Interventions to Improve Self-Management in HIV/AIDS Patients: A Scoping Review - Sevana Christina Mayaut; Untung Sujianto; Muchlis Achsan Udji (GLOBAL HEALTH SCIENCE GROUP, 2024)
Data from the Ministry of Health states that 23% of people living with HIV/AIDS (PLWHA) experience drug withdrawal. Self-management refers to managing disease needs, activating social support, and living with a chronic disease. Self-management has also been shown to control patients' adherence to medication so that it can increase CD4 counts in PLWHA and improve some clinical symptoms. Specific therapy for HIV cases has not been found to cure HIV infection, but HIV self-management can slow down or prevent the occurrence of more severe conditions. Based on this, self-management is very important for HIV/AIDS patients. This study aims to determine interventions that can improve self-management in HIV/AIDS patients. Methods: Literature sources were obtained through searches using the Scopus, Science Direct, Google Scholar, and PubMed databases with the last 5 years of research (2018-2023). The keywords used in the search were intervention, self-management, and HIV/AIDS. The search equation was applied without limitation, taking into account the title, abstract, interventions, and methods used. Articles that had been obtained were then analyzed for differences and duplication. A chart for visual representation of how the search and selection of articles was made PRISMA-SR flow diagram. Data extraction was done by creating tables. Results: interventions used to improve self-management in HIV/AIDS patients include self-management applications, spiritual counseling, and prayer therapy. Conclusion: The interventions used were proven to improve self-management in HIV/AIDS patients.